VALIDATION OF ANTI-KINETOSE READING GLASSES IN VEHICLES: RANDOMIZED CLINICAL TRIAL - de Queiroz Cunha, Letícia; José de Oliveira Filho, Laércio; Nogueira de Araújo, Anne Isabelle; Menezes do Rego, Amália Cinthia; Araújo Filho, Irami; Santos de Medeiros, Kleyton; Irochima Pinheiro, Francisco (Revista Interfaces: Saúde, Humanas e Tecnologia, 2025)
Motion sickness, better known as motion sickness, is a common and complex syndrome that occurs in response to real or perceived movement. The objective of the study is to test the effectiveness of motion sickness goggles in individuals who have proven to have this condition and are not taking medications to prevent any symptoms of the disease. This is a Single-Blind Randomized Clinical Trial involving the participation of 10 volunteers, in two trips in a motor vehicle, one of them wearing functional motion sickness goggles , purchased online, and the other wearing adulterated goggles, also purchased online. Nausea, headache and dizziness were the most significant complaints among the participants, in addition, the number of mild to moderate symptoms was higher when using adulterated goggles. The functional goggles were able to prevent the occurrence of the reported symptoms: pressure in the eye, malaise and drowsiness; as well as reducing the frequency of headache and dizziness.